Constraining the process of Eoarchean TTG formation in the Itsaq Gneiss Complex, southern West Greenland - Hoffmann, J. Elis; Nagel, Thorsten J.; Muenker, Carsten; Naeraa, Tomas; Rosing, Minik T. (ELSEVIER, 2014)
We present new major and trace element, high-precision high-field-strength-element, hafnium and neodymium isotope data for well preserved Eoarchean TTGs within the Itsaq Gneiss Complex (IGC) of southern West Greenland. These data are combined with thermodynamic model predictions of partial melting and fractional crystallization to gain new insights into continental crust formation in the Archean. Our results show that the observed compositional range of Eoarchean TTGs can be explained by a combination two processes: (1) 5-25% partial melting of amphibolite within thickened mafic crust and (2) subsequent fractional crystallization processes. The Eoarchean TTG suite of SW Greenland probably formed through mixing of melt batches that originally formed at different source depths between 10 and 14 kbar and ponded as plutons at mid-crustal levels. The trace element compositions of some TTGs point to subsequent fractional crystallization processes involving plagioclase, clinopyroxene, amphibole and garnet. Our model is consistent with recent studies proposing that the Eoarchean Itsaq Gneiss Complex TTGs from the IGC formed by re-working of mafic protocrust that stabilized as accreted juvenile crustal terranes in the Eoarchean. The model is also in good agreement with field observations from the area. (C) 2013 Elsevier B.V. All rights reserved.